PENGARUH STRUKTUR ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN KONFLIK SEBAGAI VARIABEL MODERASI - -, Sunarmi -; Widajanti, Erni - (Universitas Slamet Riyadi, 2011)
ABSTRACT Aim of this research is to know influence organization structure to officer performance and influence organization structure to officer performance that moderate conflict. This research take location at Dinas Sosial Tenaga Kerja Dan Transmigrasi of Karanganyar Regency, regency with reason of that the office has merger so available adequate data in order to supporting this research. Population in this research is all officer of Dinas Sosial Tenaga Kerja Dan Transmigrasi Of Karanganyar Regency counted 115 people and all as sample. Data collecting done with questionnaire, observation, bibliography study and documentation. Technique analyzed data the used t test, F test, determination test, Frucot dan Sharon Test. Result of research: value t test of organization structure result 8,479 with p-value 0,000 < 0,05 that means organization structure have influence to performance. Thats mean’s, the first hipotesis can be actually. Result interaction test of organization structure with conflict |X1-X2| result value -1,887 with p value 0,062 > 0,05. Thats mean’s, the second hipotesis can’t be actually. But, R2 result show that conflict can strong influence organization structure to performance. Keywords: organization structure, conflict, performance.